Comparison of oral versus intravenous etoposide in the management of small‐cell lung cancer; A real‐world, population‐based study. (7th September 2020) - Karachiwala, Hatim; Tilley, Derek; Abdel‐Rahman, Omar; Morris, Don
Abstract: Background: We looked at the utility of PO versus IV etoposide for first‐line treatment in combination with a platinum agent (cisplatin/carboplatin) for Small‐Cell Lung Cancer (SCLC). Methods: Patients with SCLC in Alberta from 2008 to 2015 were identified through the registry. Patients were separated on the basis of stage; limited disease (LD) and extensive disease (ED). Chemotherapy naïve patients receiving one cycle of combination chemotherapy, route of etoposide administration, dose reductions and vital status was noted. Survival was assessed using log‐rank method and Kaplan‐Meyer model Results: About 2066 patients were identified with SCLC. N = 762 were diagnosed with LD and n = 1264 with ED. Patient characteristics were well balanced between age and sex among the two treatment groups. LS‐SCLC: No statistically significant difference in overall survival (OS) between IV versus PO Etoposide (17.5 months vs 17.9 months). More dose reductions were seen in the PO group as compared to the IV group (32.5% vs 21.9% P = 0.095). ES‐SCLC: There was a nonsignificant numerical difference in OS in IV versus PO Etoposide (8.7 months vs 9.7 months P = 0.124). More dose reductions were noted in the PO group as compared to the IV group (35.3% vs 21.1%). Conclusion: The two dosing schemes (PO and IV) yield similar OS in ES and LS SCLC, however, patients in the PO arm did require more dose modifications. Suggesting that PO etoposide may be equivalent and lead to similar outcomes as IV, however, more toxic but saving the patients multiple visits to the chemotherapy suite. Further analyses on cost efficacy and quality of life are required.